Amine-functionalized MIL-101(Cr) embedded with Co(ii) phthalocyanine as a durable catalyst for one-pot tandem oxidative A3 coupling reactions of alcohols. (16th February 2018) - Shaabani, Ahmad; Mohammadian, Reza; Hashemzadeh, Alireza; Afshari, Ronak; Amini, Mostafa M.
Abstract : In this study, we report a metal–organic framework (MIL-101(Cr)-NH2 ) postsynthetically modified via covalent immobilization of cobalt(ii ) phthalocyanine as an efficient and mild catalytic system. Abstract : A novel porous postsynthetic-modified metal–organic framework (MIL-101(Cr)-NH2 ) was fabricated via covalent immobilization of cobalt(ii ) phthalocyanine and characterized by a variety of techniques, including FTIR, XRD, TGA, SEM, EDS and ICP-OES analyses. This catalyst was successfully used in one-pot tandem oxidative A 3 coupling reactions of alcohols. The main advantages of this protocol are the reusability of the catalyst, operational simplicity, mild reaction conditions and high yields.